Improving The Quality of Life of The Elderly Through Body Mass Index Screening in Malang - Masfi, Achmad; Evi, Nurul; Sunaryo, Eri Yanuar Akhmad Budi; Rahmatika, Qory Tiffani; Widjayanti, Yhenti; Ramadhan, Muhammad Putra; Afiani, Nurma; Ugsang Acob, Joel Rey (Inovasi Lokal, 2023)
Introduction: The welfare of the elderly can be reflected through their health conditions, both physically, spiritually, and socially, which allows everyone to live a productive life socially and economically. Modern lifestyles have changed human attitudes and behaviors, including diet, smoking, alcohol consumption and drugs as a lifestyle so that patients with degenerative diseases (diseases due to decreased organ function) are increasing and threatening lives. Purpose: The purpose of this community service is to screen the Body Mass Index (BMI) the elderly. Methods: The methods used are measurement and examination as well as providing education. The methods used are measurement and examination as well as providing education. The method of measuring Body Mass Index and counseling about healthy lifestyles for the elderly in Malang. Results: The results of the screening conducted, of the 55 participants who took part in the examination, found 19 people were often active, 11 people experienced problems related to physical activity with infrequent activity, and 15 people experienced problems very rarely active. Conclusions: This community service runs smoothly and can provide benefits to the community. The results of this community service can be used as a reference for improving the health status of the elderly